Ferritic-austenitic duplex stainless steel material
By reducing the content of C and N, controlling the stability and proportion of the austenite phase, combined with the TRIP effect, the problem of insufficient ductility of the existing ferrite-austein system duplex stainless steel is solved, and the softness and Highly ductile ferrite-austeiner system duplex stainless steel.
Patent Information
- Application Number
- CN202380047406.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-07
- Filing Date
- 2023-09-21
- Publication Date
- 2025-02-07
AI Technical Summary
While the existing ferrite-austeiner system duplex stainless steel materials have reduced ductility while increasing their strength, and increasing the content of N leads to excessive high strength, making it difficult to meet the needs of soft and high ductility.
By reducing the content of C and N, the corrosion resistance of duplex stainless steel is ensured and the austenite phase is softened; the Md of duplex stainless steel and austenite phase is controlled within the specified range to improve the austenite phase The stability of the TRIP effect achieves high ductility; reduces the content of austenite-generating elements, saves alloying, and suppresses excessive TRIP effect to soften.
It achieves the effect of softness and high ductility compared with previous ferrite-austeiner duplex stainless steel, and is suitable for applications requiring good processability and high corrosion resistance.
Smart Images

Figure BDA0005189866270000181 
Figure BDA0005189866270000201 
Figure BDA0005189866270000221
Abstract
Description
Technical Field
[0001] The present invention relates to a ferrite-austenite duplex stainless steel material. Background Art
[0002] Ferrite-austenite duplex stainless steel is used as building materials, structural materials, etc. because of its excellent corrosion resistance and high strength. On the other hand, ferrite-austenite duplex stainless steel has lower ductility than general-purpose austenite stainless steel such as SUS304, so its application in applications requiring processability is limited. In addition, from the perspective of cost reduction, there is also a demand for lean (alloy-saving) ferrite-austenite duplex stainless steel that seeks to reduce alloy elements. Therefore, the development of lean ferrite-austenite duplex stainless steel with excellent ductility is underway.
[0003] For example, Patent Document 1 proposes a ferrite-austenite duplex stainless steel material, which contains, by mass%, C: 0.05% or less, Si: 1% or less, Mn: 2-8%, P: 0.1% or less, S: 0.02% or less, Cr: 15-23%, Mo: 4% or less, Ni: 3.0% or less, Cu: 2% or less, N: 0.05-0.3%, and the remainder is composed of Fe and unavoidable impurities, and the Cr equivalent and Ni equivalent satisfy a prescribed relationship. It is described that the duplex stainless steel material can improve ductility by optimizing the Cr equivalent and the Ni equivalent.
[0004] In addition, Patent Document 2 proposes a ferrite-austenite duplex stainless steel material, which contains, by mass%, C: 0.08% or less, Si: 0.7-1.1%, Mn: 2.4-3.5%, Cr: 17.9-20.7%, Ni: 0.05-1.15%, N: 0.18-0.3%, Cu: 0.4-2.8%, and the remainder is composed of Fe and unavoidable impurities, and the pitting potential predicted by the prescribed formula is 360-440 mV. It is described that the duplex stainless steel material can improve ductility by optimizing the content of alloy components such as Ni, Si, Mn, and Cu.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2012-126992
[0008] Patent Document 2: Japanese Patent Application No. 2019-501286 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The ferrite-austenite duplex stainless steel materials described in Patent Documents 1 and 2 are both improved in strength by reducing the Ni content while increasing the Mn and N contents. However, if the N content is increased, the ferrite-austenite duplex stainless steel material becomes excessively strong, and ductility may be reduced.
[0011] Therefore, an object of the present invention is to provide a ferrite-austenite duplex stainless steel material which is softer and has higher ductility than conventional ferrite-austenite duplex stainless steel materials.
[0012] Means for solving problems
[0013] The inventors of the present invention have continued to conduct intensive studies on a lean ferrite-austenite duplex stainless steel material in order to solve the above-mentioned problems, and as a result, have obtained the following findings (1) to (3).
[0014] (1) By reducing the contents of C and N, the austenite phase can be softened while ensuring the corrosion resistance of the duplex stainless steel material.
[0015] (2) By controlling the Md of the duplex stainless steel material and the austenite phase within a predetermined range, the stabilization degree of the austenite phase can be increased, and the ductility can be increased by the TRIP (Transformation Induced Plasticity) effect.
[0016] (3) By reducing the content of austenite-forming elements (C, N, Ni, etc.), it is possible to soften the steel while reducing alloying and suppressing excessive TRIP effect.
[0017] Then, based on the above findings, the inventors of the present invention have found that the above problems can be solved by controlling the composition and Md of the ferrite-austenite duplex stainless steel material and at the same time controlling the ratio and Md of the austenite phase, and have completed the present invention.
[0018] That is, the present invention relates to a ferrite-austenite duplex stainless steel material having the following composition: containing, by mass, C: 0.001-0.050%, Si: 0.01-0.50%, Mn: 1.0-4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5-3.5%, Cr: 19.6-24.0%, Mo: 0.01-1.00%, Cu: 0.01-1.20%, N: 0.010-0.090%, C+N is less than 0.130%, and the remainder is composed of Fe and impurities,
[0019] The value of Md represented by the following formula (1) is 50.0 to 150.0°C:
[0020] Md=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)
[0021] (In the formula, the element symbol represents the content (mass %) of each element)
[0022] A metal structure having an austenite phase of 25 to 49 volume %,
[0023] The value of Md represented by the above formula (1) of the above austenite phase is 35.0 to 100.0°C.
[0024] Effects of the Invention
[0025] According to the present invention, it is possible to provide a ferrite-austenite duplex stainless steel material which is softer and has higher ductility than conventional ferrite-austenite duplex stainless steel materials. DETAILED DESCRIPTION
[0026] The present invention is not limited to the following embodiments, and appropriate changes and improvements to the following embodiments based on the common knowledge of those skilled in the art without departing from the gist of the present invention should also be understood to fall within the scope of the present invention.
[0027] In addition, the expression "%" about a component in this specification means "mass %" unless otherwise specified.
[0028] The ferrite-austenite duplex stainless steel material (hereinafter referred to as "duplex stainless steel material") according to an embodiment of the present invention has a composition containing C: 0.001 to 0.050%, Si: 0.01 to 0.50%, Mn: 1.0 to 4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5 to 3.5%, Cr: 19.6 to 24.0%, Mo: 0.01 to 1.00%, Cu: 0.01 to 1.20%, N: 0.010 to 0.090%, C+N is less than 0.130%, and the remainder is composed of Fe and impurities.
[0029] Here, the so-called "stainless steel material" in this specification refers to a material formed of stainless steel, and the material shape is not particularly limited. Examples of material shapes include plate-shaped (including strip-shaped), rod-shaped, tubular, etc. In addition, the cross-sectional shape can also be various steel sections such as T-shaped and I-shaped.
[0030] In addition, the term "ferrite-austenite system" as used herein refers to a metal structure that is mainly a dual phase of a ferrite phase and an austenite phase at room temperature. Therefore, the term "ferrite-austenite system" also includes a phase other than austenite phase (e.g., martensite phase) that contains a small amount of ferrite phase and austenite phase.
[0031] Furthermore, the so-called "impurities" in this specification refer to components mixed in due to various main factors of raw materials such as ores and waste materials and manufacturing processes when stainless steel materials are manufactured industrially, and are allowed within the range that does not cause adverse effects on the present invention. For example, impurities also include unavoidable impurities. As impurities, for example, O can be cited. The content of O is, for example, 0.0001 to 0.0070%.
[0032] In addition, regarding the content of each element, "xx% or less" means that it is xx% or less, but includes an amount exceeding 0% (particularly exceeding the impurity level).
[0033] The duplex stainless steel material according to the embodiment of the present invention may further contain one or more selected from Nb: 0.010 to 0.500%, Ti: 0.01 to 0.50%, V: 0.01 to 0.50%, W: 0.05 to 0.50%, Co: 0.01 to 0.30%, B: 0.0002 to 0.0050%, Sn: 0.010 to 0.500%, Al: 0.010 to 0.050%, Mg: 0.0002 to 0.0100%, Ca: 0.0002 to 0.0100%, Ta: 0.050% or less, Ga: 0.050% or less, Zr: 0.01 to 0.50%, and REM: 0.0002 to 0.0100%, as needed.
[0034] Each component is described in detail below.
[0035] <C:0.001~0.050%>
[0036] C is an element that has a great influence on the stability of the austenite phase. If the C content is too much, it is possible that the ductility (workability) is reduced, or the precipitation of Cr carbides is promoted to cause intergranular corrosion. Therefore, the C content is set to 0.050% or less, preferably 0.045% or less, more preferably 0.040% or less, further preferably 0.35% or less, and particularly preferably 0.030% or less. In addition, from the perspective of corrosion resistance, it is better to have a lower C content, but if the C content is excessively reduced, it will lead to an increase in cost. Therefore, the C content is set to 0.001% or more, preferably 0.002% or more, and more preferably 0.005% or more.
[0037] <Si:0.01~0.50%>
[0038] Si is an element added as a deoxidizing element and is also useful for improving oxidation resistance. However, if the content of Si is excessive, hardening occurs and ductility decreases. Therefore, the content of Si is made 0.50% or less, preferably less than 0.50%, more preferably 0.45% or less, and further preferably 0.40% or less. In addition, if Si is excessively reduced, the cost during smelting increases. Therefore, the content of Si is made 0.01% or more, preferably 0.02% or more, and more preferably 0.05% or more.
[0039] <Mn: 1.0 to 4.5%>
[0040] Mn is an element that concentrates in the austenite phase and plays an important role in stabilizing the austenite phase. However, if the content of Mn is excessive, not only does ductility decrease, but corrosion resistance and hot workability also decrease. Therefore, the content of Mn is made 4.5% or less, preferably 4.0% or less, and more preferably 3.5% or less. In addition, if Mn is excessively reduced, the cost during smelting increases. Therefore, the content of Mn is made 1.0% or more, preferably 1.1% or more, and more preferably 1.2% or more.
[0041] <P: 0.050% or less>
[0042] P is an element contained in raw materials such as Cr. If the content of P is high, formability decreases. Therefore, the content of P is made 0.050% or less, preferably 0.045% or less, and more preferably 0.040% or less. On the other hand, although the content of P is preferably low, reducing the content of P has a limit. The lower limit value of the P content is generally 0.001%, preferably 0.002%, and more preferably 0.003%.
[0043] <S: 0.030% or less>
[0044] S is an element contained in various raw materials. S combines with Mn to form inclusions, which may become the starting point of rust. Therefore, the lower the content of S, the higher the corrosion resistance. Therefore, the content of S is made 0.030% or less, preferably 0.025% or less, and more preferably 0.020% or less. On the other hand, reducing the content of S has a limit. The lower limit value of the S content is generally 0.0001%, preferably 0.0005%.
[0045] <Ni: 1.5 to 3.5%>
[0046] Ni is an austenite-generating element and an important element for adjusting the stability of the austenite phase. In addition, Ni also has the effect of inhibiting the precipitation of nitrides and improving corrosion resistance. In order to exert these effects, the Ni content is set to 1.5% or more, preferably 1.6% or more, more preferably 1.7% or more, and further preferably 1.8% or more. On the other hand, if the Ni content is too much, it will not only lead to an increase in raw material costs, but also may cause problems such as stress corrosion cracking due to the increased proportion of the austenite phase. Therefore, the Ni content is set to 3.5% or less, preferably 3.4% or less, and more preferably 3.0% or less.
[0047] <Cr:19.6~24.0%>
[0048] Cr is an element necessary for ensuring corrosion resistance. In order to exert this effect, the Cr content is 19.6% or more, preferably 20.0% or more, and more preferably 20.4% or more. On the other hand, if the Cr content is too high, hot working cracking or an increase in the cost of the refining process will occur. Therefore, the Cr content is 24.0% or less, preferably 23.5% or less, and more preferably 23.0% or less.
[0049] <Mo:0.01~1.00%>
[0050] Mo is an element that improves corrosion resistance. In order to exert this effect, the content of Mo is set to 0.01% or more, preferably 0.03% or more, and more preferably 0.05% or more. On the other hand, if the content of Mo is too high, the cost of raw materials will increase. Therefore, the content of Mo is set to 1.00% or less, preferably 0.80% or less, and more preferably 0.50% or less.
[0051] <Cu:0.01~1.20%>
[0052] Cu is an austenite-forming element like Mn and Ni, and has the effect of inhibiting the precipitation of nitrides to improve corrosion resistance. In order to exert these effects, the Cu content is 0.01% or more, preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, if the Cu content is too much, it not only leads to an increase in raw material costs, but also reduces hot workability. Therefore, the Cu content is 1.20% or less, preferably 1.00% or less, and more preferably 0.80% or less.
[0053] <N:0.010~0.090%>
[0054] N, like C, is an element that has a significant impact on the stability of the austenite phase. Additionally, N is also an element that improves corrosion resistance through solid solution. To achieve these effects, the content of N is 0.010% or more, preferably 0.020% or more. On the other hand, if the content of N is excessive, the ductility decreases, and the corrosion resistance also decreases due to the precipitation of Cr nitrides. Therefore, the content of N is 0.090% or less, preferably 0.080% or less, and more preferably 0.075% or less.
[0055] <C + N: less than 0.130%>
[0056] If the total content of C and N increases, the corrosion resistance decreases due to sharpening, or the ductility decreases due to high strength. Therefore, the total content of C and N is less than 0.130%, preferably less than 0.120%, and more preferably 0.110% or less. In addition, the lower limit value of the total content of C and N is not particularly limited, but it is preferably 0.010%, preferably 0.020%, and more preferably 0.030%.
[0057] <Nb: 0.010 - 0.500%>
[0058] Nb forms nitrides (NbN) or carbides (NbC), which have the effect of improving workability. To achieve this effect, the content of Nb is 0.010% or more, preferably 0.015% or more, and more preferably 0.020% or more. On the other hand, if the content of Nb is excessive, the ductility decreases. Therefore, the content of Nb is 0.500% or less, preferably 0.300% or less, and more preferably 0.200% or less.
[0059] <Ti: 0.01 - 0.50%>
[0060] Ti, like Nb, also forms nitrides (TiN) or carbides (TiC), which have the effect of improving workability. To achieve this effect, the content of Ti is 0.01% or more, preferably 0.015% or more, and more preferably 0.02% or more. On the other hand, if the content of Ti is excessive, the ductility decreases. Therefore, the content of Ti is 0.50% or less, preferably 0.30% or less, and more preferably 0.20% or less.
[0061] <V: 0.01 - 0.50%>
[0062] V forms nitrides, which have the effect of improving workability. To achieve this effect, the content of V is 0.01% or more, preferably 0.03% or more, and more preferably 0.05% or more. On the other hand, if the content of V is excessive, the ductility and hot workability decrease. Therefore, the content of V is 0.50% or less, preferably 0.45% or less, and more preferably 0.40% or less.
[0063] <W:0.05~0.50%>
[0064] W is an element effective in improving corrosion resistance. In order to exert this effect, the W content is set to 0.05% or more, preferably 0.08% or more, and more preferably 0.10% or more. On the other hand, if the W content is too much, ductility decreases. Therefore, the W content is set to 0.50% or less, preferably 0.45% or less, and more preferably 0.40% or less.
[0065] <Co:0.01~0.30%>
[0066] Co is an element effective for improving high temperature strength and hot workability. In order to exert these effects, the content of Co is set to 0.01% or more, preferably 0.03% or more, and more preferably 0.05% or more. On the other hand, if the content of Co is too much, the toughness decreases. Therefore, the content of Co is set to 0.30% or less, preferably 0.25% or less, and more preferably 0.20% or less.
[0067] <B:0.0002~0.0050%>
[0068] B is an element that segregates at the grain boundaries to improve hot workability. In order to exert this effect, the B content is set to 0.0002% or more, preferably 0.0010% or more, and more preferably 0.0015% or more. On the other hand, if the B content is too high, the corrosion resistance is significantly reduced. Therefore, the B content is set to 0.0050% or less, preferably 0.0040% or less, and more preferably 0.0030% or less.
[0069] <Sn:0.010~0.500%>
[0070] Sn is an element that improves corrosion resistance. In order to exert this effect, the content of Sn is set to 0.010% or more, preferably 0.020% or more, and more preferably 0.030% or more. On the other hand, if the content of Sn is too much, hot workability decreases. Therefore, the content of Sn is set to 0.500% or less, preferably 0.450% or less, and more preferably 0.400% or less.
[0071] <Al:0.010~0.050%>
[0072] Al is an element effective for desulfurization and deoxidation. To exert these effects, the content of Al is 0.010% or more, preferably 0.015% or more, and more preferably 0.020% or more. On the other hand, if the content of Al is excessive, it will lead to an increase in manufacturing defects and raw material costs. Therefore, the content of Al is 0.050% or less, preferably 0.045% or less, and more preferably 0.040% or less.
[0073] <Mg: 0.0002 - 0.0100%>
[0074] Mg is an element that not only deoxidizes but also has the effect of refining the solidification structure. To exert these effects, the content of Mg is 0.0002% or more, preferably 0.0005% or more, and more preferably 0.0010% or more. On the other hand, if the content of Mg is excessive, it will lead to an increase in raw material costs. Therefore, the content of Mg is 0.0100% or less, preferably 0.0095% or less, and more preferably 0.0090% or less.
[0075] <Ca: 0.0002 - 0.0100%>
[0076] Ca is an element effective for desulfurization and deoxidation. To exert these effects, the content of Ca is 0.0002% or more, preferably 0.0005% or more, and more preferably 0.0010% or more. On the other hand, if the content of Ca is excessive, hot working cracking is likely to occur and the corrosion resistance is also reduced. Therefore, the content of Ca is 0.0100% or less, preferably 0.0080% or less, and more preferably 0.0050% or less.
[0077] <Ta: 0.050% or less>
[0078] Ta is an element that improves corrosion resistance through modification of inclusions. However, if the content of Ta is excessive, it will lead to a decrease in room temperature ductility and toughness. Therefore, the content of Ta is 0.050% or less, preferably 0.045% or less, and more preferably 0.040% or less. On the other hand, the lower limit value of the content of Ta is not particularly limited, but to exert the effects brought by Ta, it is preferably 0.001%, and more preferably 0.003%.
[0079] <Ga: 0.050% or less>
[0080] Ga is an element that improves corrosion resistance and suppresses hydrogen embrittlement. However, if the Ga content is too high, workability decreases. Therefore, the Ga content is 0.050% or less, preferably 0.040% or less, and more preferably 0.030% or less. On the other hand, the lower limit of the Ga content is not particularly limited, but in order to volatilize the effect brought by Ga, it is preferably 0.001%, and more preferably 0.003%.
[0081] <Zr:0.01~0.50%>
[0082] Zr is an element that has similar effects to Nb and Ti and improves oxidation resistance. In order to exert these effects, the Zr content is set to 0.01% or more, preferably 0.03% or more, and more preferably 0.05% or more. On the other hand, if the Zr content is too high, not only the ductility is reduced, but also the raw material cost is increased. Therefore, the Zr content is set to 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.
[0083] <REM:0.0002~0.0100%>
[0084] REM (rare earth) is an element effective in improving hot workability. In order to exert this effect, the content of REM is set to 0.0002% or more, preferably 0.0005% or more, and more preferably 0.0010% or more. On the other hand, if the content of REM is too high, the manufacturability is impaired and the cost is increased. Therefore, the content of REM is set to 0.0100% or less, preferably 0.0090% or less, and more preferably 0.0080% or less.
[0085] In addition, REM is a general term for Sc, Y, and 15 elements (lanthanoids) of La to Lu. As REM, these elements can be used alone or in combination of two or more.
[0086] The value of Md represented by the following formula (1) of the duplex stainless steel material according to the embodiment of the present invention is 50.0 to 150.0°C, preferably 55.0 to 140.0°C, more preferably 60.0 to 130.0°C, and further preferably 70.0 to 120.0°C.
[0087] Md=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)
[0088] In formula (1), the element symbols represent the content (mass %) of each element.
[0089] Here, Md is an index indicating the stability of the austenite phase. The larger the value of Md (high temperature), the more unstable the austenite phase is. If the value of Md is lower than 50.0°C, the stability of the austenite phase is too high, so it becomes difficult to transform the austenite phase into a processing-induced martensite phase, and the desired strength and ductility cannot be obtained. On the other hand, if the value of Md exceeds 150.0°C, the amount of processing-induced martensite phase transformed from the austenite phase increases, so the strength is excessively high and the desired ductility cannot be obtained.
[0090] The duplex stainless steel material of the embodiment of the present invention has the following metal structure: the austenite phase is 25 to 49 volume %, preferably 25 to 47 volume %, more preferably 25 to 40 volume %, further preferably 26 to 38 volume %, and particularly preferably 28 to 37 volume %. If the austenite phase is less than 25 volume %, the proportion of the ferrite phase increases, so the desired ductility cannot be obtained. On the other hand, if the austenite phase exceeds 49 volume %, the strength is excessively high, and the desired ductility cannot be obtained. In addition, by controlling the austenite phase to less than 40 volume %, the average grain size of the ferrite phase becomes easy to control more.
[0091] Here, in this specification, the ratio of the austenite phase in the duplex stainless steel can be obtained using EBSD (backscattered electron diffraction). Specifically, the EBSD measurement is performed using a sample that has been mirror-polished on a thickness direction cross section parallel to the rolling direction of the duplex stainless steel. For the data obtained by the EBSD measurement, an analysis software is used to create a phase ratio diagram, separate the ferrite phase and the austenite phase, and obtain the ratio of the austenite phase.
[0092] The value of Md represented by the above formula (1) of the austenite phase is 35.0 to 100.0°C, preferably 40.0 to 95.0°C, more preferably 50.0 to 90.0°C, further preferably 52.0 to 85.0°C, and particularly preferably 53.0 to 80.0°C. If the value of Md of the austenite phase is lower than 35.0°C, it becomes difficult to transform the austenite phase into a work-induced martensite phase, and it is difficult to obtain the desired strength and ductility. On the other hand, if the value of Md of the austenite phase exceeds 100.0°C, the amount of the work-induced martensite phase transformed from the austenite phase increases, so the strength is excessively high, and it is difficult to obtain the desired ductility.
[0093] Here, in this specification, the content of each element in the austenite phase used for calculating the Md of the austenite phase can be measured by EPMA (electron probe microanalyzer). Specifically, a sample mirror-polished in the thickness direction section of the duplex stainless steel material parallel to the rolling direction is used, and a qualitative analysis is performed using EPMA. Since C and N have the characteristics of being concentrated in the austenite phase, the qualitative mapping of C or N is performed on the entire cross section to determine the austenite phase. Then, C, N, Si, Mn, Cr, Ni, Cu and Mo are quantitatively analyzed in the approximate center of the austenite phase in a manner that the electron beam does not touch the ferrite phase. The quantitative analysis is performed at more than 3 points, and its average value is used as the result of the content of each element.
[0094] The average grain size of the ferrite phase of the duplex stainless steel material according to the embodiment of the present invention is preferably 7.0 μm or more, more preferably 7.1 μm or more, and further preferably 7.2 μm or more. If the average grain size of the ferrite phase is less than 7.0 μm, it is difficult to obtain the desired ductility. The upper limit of the average grain size of the ferrite phase is not particularly limited, but is typically 20.0 μm, preferably 18.0 μm, and more preferably 15.0 μm.
[0095] Here, in this specification, the average grain size of the ferrite phase in the duplex stainless steel material can be obtained by EBSD measurement. Specifically, the EBSD measurement is performed using a sample mirror-polished in a thickness direction cross section parallel to the rolling direction of the duplex stainless steel material. For the data obtained in the EBSD measurement, the area of the ferrite phase (BCC) grains can be obtained by the area fraction method.
[0096] The value of DF represented by the following formula (2) of the duplex stainless steel material according to the embodiment of the present invention is preferably 50.0 to 80.0, more preferably 54.0 to 80.0, further preferably 60.0 to 80.0, particularly preferably 63.0 to 78.0, and most preferably 65.0 to 75.0.
[0097] DF=7.2(Cr+0.88Mo+0.78Si)-8.9(Ni+0.03Mn+0.72Cu+22C+21N)-44.9(2)
[0098] In formula (2), the element symbols represent the content (mass %) of each element.
[0099] Here, DF is an index indicating the amount of ferrite phase. Therefore, 100-DF is the amount of austenite phase. However, since DF is an index determined based on the content of elements, it should be noted that it is inconsistent with the amount of austenite phase actually measured. If the value of DF is less than 50.0, the strength is excessively high and it is difficult to obtain the desired ductility. On the other hand, if the value of DF exceeds 80.0, the proportion of ferrite phase increases, so it is difficult to obtain the desired ductility.
[0100] The duplex stainless steel material according to the embodiment of the present invention preferably has a tensile strength of 800 MPa or less, more preferably 790 MPa or less, and further preferably 780 MPa or less. If the tensile strength is within this range, it can be said that it is softer than conventional duplex stainless steel materials, and thus the desired ductility can be ensured. In addition, the lower limit of the tensile strength is not particularly limited, but is generally 500 MPa, preferably 550 MPa.
[0101] Here, the tensile strength of the duplex stainless steel material can be measured in accordance with JIS Z2241:2011.
[0102] The duplex stainless steel material according to the embodiment of the present invention preferably has a uniform elongation of 30.0% or more, more preferably 31.0% or more, and even more preferably 32.0% or more. If the uniform elongation is within such a range, it can be said that the ductility is excellent compared with the conventional duplex stainless steel material. In addition, the upper limit of the uniform elongation is not particularly limited, but is generally 50.0%, preferably 48.0%, and more preferably 45.0%.
[0103] Here, the uniform elongation of the duplex stainless steel material can be measured in accordance with JIS Z2241: 2011. The uniform elongation is obtained as the permanent elongation to the maximum tensile load.
[0104] The duplex stainless steel material according to the embodiment of the present invention has a -4 ~8.3×10 -3 s -1 When a tensile test is performed at a strain rate of 15 to 20%, the ratio of the n value in the strain region of 15 to 20% to the n value in the strain region of 20 to 25% is preferably 0.80 or less, more preferably 0.79 or less. If the n value ratio is within this range, it can be said that the ductility is excellent under general processing conditions. In addition, the lower limit of the n value ratio is not particularly limited, but is generally 0.01, preferably 0.10. In addition, the strain rate affects the processing heat, so the size of the TRIP effect changes. For example, if the strain rate is large, the processing heat increases, so the TRIP effect becomes smaller and the ductility decreases.
[0105] Here, the n value of the duplex stainless steel material can be measured in accordance with JIS Z2241:2011.
[0106] The 0.2% yield strength of the duplex stainless steel material according to the embodiment of the present invention is preferably 480 MPa or less, more preferably 470 MPa or less. If the 0.2% yield strength is within this range, the duplex stainless steel material can be said to be soft. In addition, the lower limit of the 0.2% yield strength is not particularly limited, but is generally 300 MPa, preferably 350 MPa.
[0107] Here, the 0.2% yield strength of the duplex stainless steel material can be measured in accordance with JIS Z2241:2011.
[0108] The duplex stainless steel material according to the embodiment of the present invention may be a hot-rolled material or a cold-rolled material. In addition, the hot-rolled material or the cold-rolled material may be subjected to annealing and pickling.
[0109] The thickness of the duplex stainless steel material according to the embodiment of the present invention can be appropriately adjusted according to the application, and is not particularly limited, but is generally 5.0 mm or less, preferably 4.0 mm or less, and more preferably 3.0 mm or less. In addition, when the duplex stainless steel material is in the shape of a rod, the thickness refers to the equivalent circle diameter of the cross section. In addition, when the duplex stainless steel material is a steel section, the thickness refers to the thickness of any part of the cross section.
[0110] The duplex stainless steel material according to the embodiment of the present invention can be set to the following two options A and B, for example.
[0111] <Scheme A>
[0112] [A1] A duplex stainless steel material having the following composition: containing, by mass, C: 0.001 to 0.050%, Si: 0.01% or more and less than 0.50%, Mn: 1.0 to 4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5 to 3.5%, Cr: 19.6 to 24.0%, Mo: 0.01 to 1.00%, Cu: 0.01 to 1.20%, N: 0.010 to 0.090%, C+N is less than 0.130%, and the remainder is Fe and impurities,
[0113] The value of Md represented by the following formula (1) is 50.0 to 150.0°C:
[0114] Md=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)
[0115] (wherein, the element symbol represents the content (mass %) of each element)
[0116] A metal structure having an austenite phase of 25 to 49 volume %,
[0117] The value of Md represented by the above formula (1) of the above austenite phase is 35.0 to 100.0°C.
[0118] [A2] The duplex stainless steel material according to [A1], further comprising, by mass, one or more selected from the group consisting of Nb: 0.010-0.500%, Ti: 0.01-0.50%, V: 0.01-0.50%, W: 0.05-0.50%, Co: 0.01-0.30%, B: 0.0002-0.0050%, Sn: 0.010-0.500%, Al: 0.010-0.050%, Mg: 0.0002-0.0100%, Ca: 0.0002-0.0100%, Ta: 0.050% or less, Ga: 0.050% or less, Zr: 0.01-0.50%, and REM: 0.0002-0.0100%.
[0119] [A3] The duplex stainless steel material according to [A1] or [A2], wherein the value of DF represented by the following formula (2) is 50.0 to 80.0:
[0120] DF=7.2(Cr+0.88Mo+0.78Si)-8.9(Ni+0.03Mn+0.72Cu+22C+21N)-44.9(2)
[0121] (In the formula, the element symbol represents the content (mass %) of each element).
[0122] [A4] The duplex stainless steel material according to any one of [A1] to [A3], which satisfies at least one of the following characteristics (a) and (b):
[0123] (a) tensile strength is 800 MPa or less;
[0124] (b) The uniform elongation is 30.0% or more.
[0125] <Scheme B>
[0126] [B1] A duplex stainless steel material having the following composition: containing, by mass, C: 0.001 to 0.040%, Si: 0.01 to 0.50%, Mn: 1.0 to 4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5 to 3.5%, Cr: 19.6 to 24.0%, Mo: 0.01 to 1.00%, Cu: 0.01 to 1.20%, N: 0.010 to 0.080%, C+N is less than 0.120%, and the remainder is Fe and impurities,
[0127] The value of Md represented by the following formula (1) is 50.0 to 150.0°C:
[0128] Md=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)
[0129] (wherein, the element symbol represents the content (mass %) of each element)
[0130] A metal structure having an austenite phase of 25 to 40 volume %,
[0131] The value of Md represented by the above formula (1) of the austenite phase is 35.0 to 100.0°C.
[0132] The average grain size of the ferrite phase is 7.0 μm or more.
[0133] [B2] The duplex stainless steel material according to [B1], further comprising, by mass, one or more selected from the group consisting of Nb: 0.010 to 0.500%, Ti: 0.01 to 0.50%, V: 0.01 to 0.50%, W: 0.05 to 0.50%, Co: 0.01 to 0.30%, B: 0.0002 to 0.0050%, Sn: 0.010 to 0.500%, Al: 0.010 to 0.050%, Mg: 0.0002 to 0.0100%, Ca: 0.0002 to 0.0100%, Ta: 0.050% or less, Ga: 0.050% or less, Zr: 0.01 to 0.50%, and REM: 0.0002 to 0.0100%.
[0134] [B3] The duplex stainless steel material according to [B1] or [B2], wherein the value of Md represented by the above formula (1) of the austenite phase is 50.0 to 90.0°C.
[0135] [B4] The duplex stainless steel material according to any one of [B1] to [B3], wherein the value of DF represented by the following formula (2) is 60.0 to 80.0:
[0136] DF=7.2(Cr+0.88Mo+0.78Si)-8.9(Ni+0.03Mn+0.72Cu+22C+21N)-44.9(2)
[0137] (In the formula, the element symbol represents the content (mass %) of each element).
[0138] [B5] The duplex stainless steel material according to any one of [B1] to [B4], wherein the -4 ~8.3×10-3 s -1 When a tensile test is performed at a strain rate of 15 to 20%, the ratio of the n value in the strain region of 20 to 25% to the n value in the strain region of 20 to 25% is 0.80 or less.
[0139] The method for producing the duplex stainless steel material according to the embodiment of the present invention is not particularly limited as long as it is a method capable of producing a duplex stainless steel material having the above-mentioned characteristics.
[0140] Hereinafter, an example of a method for producing a duplex stainless steel material according to an embodiment of the present invention (particularly, duplex stainless steel materials according to embodiments A and B) will be described.
[0141] The duplex stainless steel materials of Scheme A and Scheme B can be produced by melting the stainless steel having the above composition by vacuum melting to form a steel slab, hot rolling and annealing, and then cold rolling and finish annealing. In this production method, controlling the conditions of the heat treatment is particularly critical. The specific production method of each scheme is described below.
[0142] <Scheme A>
[0143] In duplex stainless steel, in order to control the ratio of austenite phase and Md within the specified range, it is necessary to control the conditions of heat treatment (annealing) (heating rate, reaching temperature, holding time and cooling rate). These conditions affect the solid solution state of carbon and nitrogen. In addition, the reaching temperature affects the change of thermodynamic austenite amount. Furthermore, the control of reaching temperature and holding time is also aimed at fully recrystallizing the entire structure.
[0144] Since the solid solution of carbon and nitrogen affects the proportion (production amount) and Md of the austenite phase, if they exist more as carbides and nitrides, it becomes impossible to control the proportion and Md of the austenite phase within a specified range. Therefore, in the heat treatment (annealing) process, it is necessary to suppress the precipitation of carbides and nitrides during heating and cooling, and to fully dissolve the unsolvated carbides and nitrides by maintaining the reached temperature. In addition, since the concentration of the elements (especially carbon and nitrogen) constituting the austenite phase changes due to the proportion of the austenite phase, the Md derived from this changes, so it is also necessary to adjust the reached temperature to control the proportion of the austenite phase.
[0145] The hot rolling conditions are not particularly limited and may be carried out according to a conventional method.
[0146] Regarding annealing after hot rolling, the heating rate is set to be above 20°C / second, and after being kept at a reaching temperature of 1050-1150°C for more than 10 seconds, the steel is cooled to below 400°C at a cooling rate of 20°C / second or more. Annealing under such conditions is to fully dissolve the carbides and nitrides precipitated during cooling after hot rolling, and to suppress the precipitation of carbides and nitrides during cooling after annealing. In particular, if the reaching temperature is lower than 1050°C, the solid solution of carbides and nitrides becomes insufficient, and the proportion of austenite phase becomes too much. In addition, if the reaching temperature is higher than 1150°C, although carbides and nitrides are fully dissolved, the proportion of austenite becomes too small. Furthermore, a certain amount of carbon and nitrogen are also dissolved in the ferrite phase, and it is also possible that precipitates are formed in the ferrite phase with a small solid solution limit during cooling, thereby deteriorating the corrosion resistance.
[0147] The conditions for cold rolling are not particularly limited, but the rolling reduction is preferably 50 to 90%. The rolling reduction is 50% or more in order to expand the surface area by crushing or stretching carbides and precipitates, thereby promoting solid solution during heat treatment. In addition, the rolling reduction is 90% or less in order to suppress edge cracks caused by excessive rolling. From the viewpoint of stably obtaining this effect, the rolling reduction is more preferably 85% or less.
[0148] When cold rolling is performed two or more times, intermediate annealing may be performed between each cold rolling. When intermediate annealing is performed, the conditions thereof may be based on the annealing conditions after hot rolling.
[0149] Regarding the conditions for the finish annealing, the heating rate is set to be above 20°C / second, and after being kept at a reaching temperature of 1040-1120°C for more than 5 seconds, the steel is cooled to below 850°C at a cooling rate of 30°C / second or more, and then cooled to below 400°C at a cooling rate of 20°C / second or more. The finish annealing is performed under such conditions to suppress the precipitation of carbides and nitrides during the heating process, complete recrystallization, solid solution of carbides and nitrides, control the proportion of austenite phase, suppress the change in the proportion of austenite phase during cooling, and suppress the re-precipitation of carbides and nitrides.
[0150] <Scheme B>
[0151] In duplex stainless steel, in order to control the average grain size of the ferrite phase within a specified range, it is necessary to control the conditions during hot rolling (temperature and cooling rate just after the final pass). In addition, in order to control the proportion of the austenite phase and Md within a specified range, it is necessary to control the conditions of heat treatment (annealing) (heating rate, reaching temperature, holding time and cooling rate). These conditions all affect the solid solution state of carbon and nitrogen. In addition, the reaching temperature affects the change in the thermodynamic amount of austenite. Furthermore, the control of the reaching temperature and holding time is also intended to fully recrystallize the entire structure.
[0152] Since the solid solution of carbon and nitrogen affects the proportion (production amount) and Md of the austenite phase, if they exist more as carbides and nitrides, it becomes impossible to control the proportion and Md of the austenite phase within a specified range. Therefore, in the heat treatment (annealing) process, it is necessary to suppress the precipitation of carbides and nitrides during heating and cooling, and to fully dissolve the unsolvated carbides and nitrides by maintaining the reached temperature. In addition, since the concentration of the elements (especially carbon and nitrogen) constituting the austenite phase changes due to the proportion of the austenite phase, the Md derived from this changes, so it is also necessary to adjust the reached temperature to control the proportion of the austenite phase.
[0153] In hot rolling, the temperature immediately after the final pass is set to 1030° C. or higher, and then cooled to 800° C. at a cooling rate of 20° C. / sec or higher. By hot rolling under such conditions, the grains of the ferrite phase can be coarsened and controlled within a predetermined range.
[0154] Here, there are two main reasons why the grains of the ferrite phase become smaller. The first point is the recrystallization during hot rolling or during annealing thereafter due to the accumulation of hot rolling strain. The lower the hot rolling temperature, the more strain is accumulated to induce recrystallization, and the easier it is for the grains of the ferrite phase to be refined, so it is necessary to increase the temperature to a temperature just after the final pass that is difficult to cause it. The second point is the growth inhibition of the grains of the ferrite phase due to the generation of the austenite phase. If the austenite phase is precipitated in the crystal grain boundaries of the ferrite phase, the activity of the crystal grain boundaries of the ferrite phase becomes sluggish, inhibiting grain growth. The austenite phase has a peak near 900°C and decreases as the temperature increases, so the higher the temperature, the easier it is for the grains of the ferrite phase to grow. On the other hand, in order to keep the hot rolling temperature at a high temperature, it is effective to increase the heating temperature of the slab before hot rolling and increase the rolling speed to shorten the heat dissipation time, but the fuel cost increases and the manufacturing difficulty increases. Therefore, taking these circumstances into consideration, the lower limit of the final pass temperature of hot rolling is set to 1030°C.
[0155] Regarding annealing after hot rolling, the heating rate is set to be above 20°C / second, and after being kept at an arrival temperature of 1080-1150°C for more than 10 seconds, the steel is cooled to below 400°C at a cooling rate of 20°C / second or more. Annealing under such conditions is to fully dissolve the carbides and nitrides precipitated during cooling after hot rolling, and to inhibit the precipitation of carbides and nitrides during the cooling process after annealing. In addition, the proportion of austenite phase is made relatively small, the inhibition of grain growth of ferrite phase is reduced, and it becomes easy to coarsen the grains of ferrite phase. In particular, if the arrival temperature is lower than 1080°C, the solid solution of carbides and nitrides becomes insufficient, and the proportion of austenite phase also becomes too much. In addition, if the arrival temperature is higher than 1150°C, although carbides and nitrides are fully dissolved, the proportion of austenite becomes too small. Furthermore, a certain amount of carbon and nitrogen are also dissolved in the ferrite phase, and precipitates may be formed during cooling in the ferrite phase having a small solid solubility limit, thereby deteriorating the corrosion resistance.
[0156] The conditions for cold rolling are not particularly limited, but the rolling reduction is preferably 50 to 80%. The rolling reduction is 50% or more in order to expand the surface area by crushing or stretching precipitates such as carbides, thereby promoting solid solution during heat treatment. On the other hand, the rolling reduction is 80% or less in order to suppress edge cracks caused by excessive rolling. In addition, it is also to suppress the accumulation of rolling strain that causes the structure of the finished annealed material to become too fine. As mentioned above, if there is too much strain, recrystallization is induced and the grains become fine, so this situation is avoided. From the viewpoint of stably obtaining these effects, the rolling reduction is more preferably 75% or less.
[0157] When cold rolling is performed two or more times, intermediate annealing may be performed between each cold rolling. When intermediate annealing is performed, the conditions thereof may be based on the annealing conditions after hot rolling.
[0158] Regarding the conditions for the finished product annealing, the heating rate is set to be above 20°C / second, and after being kept at a reaching temperature of 1000-1150°C for more than 5 seconds, the steel is cooled to below 850°C at a cooling rate of above 30°C / second, and then cooled to below 400°C at a cooling rate of above 20°C / second. The finished product annealing under such conditions is to: inhibit the precipitation of carbides and nitrides during the heating process, complete recrystallization, solid solution of carbides and nitrides, control the proportion of austenite phases, inhibit the change in the proportion of austenite phases during cooling, and inhibit the re-precipitation of carbides and nitrides. In addition, by controlling the structure until cold rolling, the grains of the ferrite phase are coarsened in the finished product annealing.
[0159] The duplex stainless steel material of the embodiment of the present invention is softer and more ductile than the conventional ferrite-austenite duplex stainless steel material. Therefore, the duplex stainless steel material can suppress the springback caused by excessive high strength during forming, and the shape freezing property is also good. In addition, the duplex stainless steel material is higher in strength and has excellent corrosion resistance than general-purpose austenite stainless steel materials such as SUS304. Therefore, the duplex stainless steel material can be used in various applications requiring the above-mentioned properties.
[0160] Example
[0161] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0162] <Implementation Example of Scheme A>
[0163] A cold-rolled annealed sheet was produced as a duplex stainless steel material. Specifically, stainless steel having the composition of the steel type shown in Table 1 (the remainder is Fe and impurities) was smelted by vacuum melting to form a steel slab, and then hot rolled and annealed according to a conventional method. For annealing, the heating rate was set to 30°C / second, and after being kept at an arrival temperature of 1100°C for 180 seconds, it was cooled to below 400°C at a cooling rate of 25°C / second. Next, the annealed hot-rolled sheet was cold rolled at a rolling rate of 80%, and then finished annealing was performed to obtain a cold-rolled annealed sheet with a thickness of 1.0 mm. For finished annealing, the heating rate was set to 30°C / second, and after being kept at an arrival temperature of 1080°C for 30 seconds, it was cooled to below 850°C at a cooling rate of 30°C / second, and then cooled to below 400°C at a cooling rate of 25°C / second. In addition, in Table 1, the values of Md and DF are calculated based on the content of each element. In addition, among the steel types shown in Table 1, No. 1-M and 1-N are conventional duplex stainless steel materials.
[0164] [Table 1]
[0165]
[0166] The cold rolled annealed sheets obtained above were evaluated as follows.
[0167] <Ratio of Austenite Phase (γ Phase) in Duplex Stainless Steel Material>
[0168] After cutting out the test piece from the cold-rolled annealed sheet, the cross section in the thickness direction parallel to the rolling direction is mirror-polished and EBSD (backscattered electron diffraction) is measured. Regarding EBSD measurement, by scanning electron microscope, using the measurement software TSL OIM Data Collection 7 (TSL Solutions Co., Ltd.), a 200 μm square area is measured at the center of the thickness direction of the test piece with a step length of 0.3 μm. Then, for the data obtained in the EBSD measurement, the analysis software TSL OIM Analysis 7 (TSL Solutions Co., Ltd.) is used to make a comparison diagram to separate the ferrite phase and the austenite phase. Then, the proportion of the austenite phase in the entire observation area is obtained.
[0169] <Md of Austenite Phase (γ Phase)>
[0170] After cutting out the test piece from the cold-rolled annealed sheet, the cross section in the thickness direction parallel to the rolling direction is mirror-polished, and the composition analysis is performed using EPMA (electron probe microanalyzer). Specifically, since C and N have the characteristics of being concentrated in the austenite phase, the qualitative mapping of C or N on the entire cross section is performed to determine the austenite phase. Next, C, N, Si, Mn, Cr, Ni, Cu and Mo are quantitatively analyzed in the approximate center of the austenite phase in such a way that the electron beam does not touch the ferrite phase. The measurement area is set to an area of about 2 μm square, and more than 3 points are measured in each test piece, and the average value is used as the result of the content of each element. In addition, the measurement of EPMA is set to the following conditions: the acceleration voltage is 15 kV, the current is 0.2 μA, and the step length is 0.15 μm. The Md of the austenite phase is calculated based on the content of each element obtained in this way.
[0171] <Tensile Strength and Uniform Elongation>
[0172] A JIS 13B test piece is cut out from the cold-rolled annealed sheet in such a way that the parallel portion becomes the rolling direction, and the tensile test is carried out in accordance with JIS Z2241:2011 using the test piece. The tensile test is carried out under an atmospheric atmosphere, at room temperature (25°C) and at a tensile speed of 3 mm / min. In the tensile test, the highest strength reached is taken as the tensile strength, and the elongation until the tensile strength is taken as the uniform elongation. In this evaluation, if the tensile strength is below 800 MPa, it can be said that it is softened, and if the uniform elongation is above 30.0%, it can be said that the ductility is excellent.
[0173] Table 2 shows the evaluation results.
[0174] [Table 2]
[0175]
[0176] As shown in Table 2, Examples 1-1 to 1-7 showed good results in both tensile strength and uniform elongation because the composition and Md of the cold-rolled annealed sheet (duplex stainless steel material) and the ratio and Md of the austenite phase were controlled within the prescribed ranges.
[0177] On the other hand, in Comparative Example 1-1, since the Ni content was too small and the N and C+N contents were too large, the strength was excessively high and the ductility was also insufficient.
[0178] In Comparative Example 1-2, since the Cr content was too high and the ratio of the ferrite phase increased, the ductility was insufficient.
[0179] In Comparative Example 1-3, since the Ni content was too high and the Cr content was too low, the ratio of the austenite phase increased, and thus work hardening was easily generated, resulting in excessively high strength.
[0180] In Comparative Example 1-4, the contents of Ni, Cr, and Sn were too small, while the content of Al was too large, and the Md values of the cold-rolled annealed sheet and the austenite phase were too high. Therefore, the amount of the work-induced martensite phase increased, resulting in excessively high strength, and the ductility was also insufficient.
[0181] In Comparative Example 1-5, the Si and Cr contents were too high, the Ti content was too low, the Md value of the cold-rolled annealed sheet was too low, and the proportion of the ferrite phase was too high, so the ductility was insufficient.
[0182] Comparative Examples 1-6 and 1-7 are conventional duplex stainless steel materials, and particularly have excessive contents of N. In addition, since the Md values of the cold-rolled annealed sheets and austenite phases in Comparative Examples 1-6 and 1-7 are too low, the strength is excessively high, and the ductility is also insufficient.
[0183] In Comparative Example 1-8, since the Md of the austenite phase was too low, the ductility was insufficient.
[0184] <Implementation Example of Scheme B>
[0185] A cold-rolled annealed sheet was produced as a duplex stainless steel material. The cold-rolled annealed sheet is implemented in the order of a hot rolling process, an annealing process, a cold rolling process, and a finished annealing process. Specifically, first, a stainless steel having the composition of the steel type shown in Table 3 (the remainder is Fe and impurities) is melted by vacuum melting to form a steel slab. Next, the steel slab is subjected to a hot rolling process to obtain a hot-rolled sheet with a thickness of 5 mm. In the hot rolling process, the temperature just after the final pass is set to the temperature shown in Table 4, and is cooled to 800°C by water cooling (cooling rate of 20°C / second or more). Regarding the annealing process after the hot rolling process, the heating rate is set to 25°C / second, and after being kept at a reaching temperature (annealing temperature) of 1100°C for 30 seconds, it is cooled to below 400°C by water cooling (cooling rate of 20°C / second or more). Cold rolling is performed at the rolling rate shown in Table 4 to obtain a cold-rolled sheet with a thickness shown in Table 4. In the finish annealing process, the temperature was raised at a rate of 30°C / sec, and after being held at the target temperature (annealing temperature) shown in Table 4 for 30 seconds, the steel was cooled to 400°C or less by water cooling (cooling rate of 30°C / sec or more). In Table 3, the values of Md and DF were calculated based on the content of each element.
[0186] [Table 3]
[0187]
[0188] [Table 4]
[0189]
[0190] The cold rolled annealed sheets obtained above were evaluated as follows.
[0191] <Ratio of Austenite Phase (γ Phase) in Duplex Stainless Steel Material>
[0192] The value was determined in the same manner as in Example A.
[0193] <Md of Austenite Phase (γ Phase)>
[0194] The value was determined in the same manner as in Example A.
[0195] <Average Grain Size of Ferrite Phase (α Phase) in Duplex Stainless Steel Material>
[0196] After cutting out test pieces from the cold-rolled annealed sheet, the cross-section in the thickness direction parallel to the rolling direction was mirror-polished, and EBSD (electron backscatter diffraction) measurement was performed. Regarding the EBSD measurement, using a scanning electron microscope and the measurement software TSL OIM Data Collection 7 (TSL Solutions Co., Ltd.), a region of 200 μm square was measured at a step size of 0.3 μm at the center of the test piece in the thickness direction. For the data obtained in this EBSD measurement, the area of the grains of the ferrite phase (BCC) was determined by the Area fraction method.
[0197] <n value ratio, 0.2% yield strength and uniform elongation>
[0198] JIS No. 13B test pieces were cut out from the cold-rolled annealed sheet in such a way that the parallel part was in the rolling direction, and using these test pieces, a tensile test was carried out in accordance with JIS Z2241:2011. The tensile test was carried out under an atmospheric atmosphere at room temperature (25 °C) at a tensile speed of 10 mm / min. In the tensile test, the elongation up to the maximum strength (tensile strength) was taken as the uniform elongation.
[0199] Regarding the n value, the relationship between the stress σ and the strain ε from the 0.2% yield strength to the maximum load point was measured, and the true stress and true strain were calculated from these measured values. A graph was made on a logarithmic scale with the horizontal axis as the strain (ln ε) and the vertical axis as the stress (ln σ). Then, the slope of the straight line obtained from the graph was taken as the n value. In addition, the strain rate was as shown in Table 3.
[0200] In these evaluations, if the n value ratio is 0.80 or less and the uniform elongation is 30.0% or more, it can be said that the ductility is excellent. In addition, if the 0.2% yield strength is 480 MPa or less, it can be said to be soft.
[0201] The above evaluation results are shown in Table 5.
[0202] [Table 5]
[0203]
[0204] As shown in Table 5, in Examples 2-1 to 2-7, since the composition and Md of the cold-rolled annealed sheet (duplex stainless steel) and the proportion and Md of the austenite phase were controlled within the specified ranges, the results of the n value ratio, 0.2% yield strength and uniform elongation were all good.
[0205] In contrast, in Comparative Example 2-1, since the proportion of the austenite phase was too small, the ductility was insufficient.
[0206] In Comparative Example 2-2, since the Md of the austenite phase was too high, the average grain size of the ferrite phase was small and softening was insufficient.
[0207] Comparative Example 2-3 has a large amount of C+N due to the excessive N content. In addition, since the proportion of the austenite phase is large and the Md of the austenite phase is too low, the softening and ductility are insufficient.
[0208] In Comparative Example 2-4, since the N content is too high and the Md of the cold-rolled annealed sheet is too low, the stability of the austenite phase is high and it is difficult to transform it into the work-induced martensite phase. In addition, since the Md of the austenite phase is too low, the ductility is insufficient.
[0209] In Comparative Example 2-5, since the ratio of the austenite phase was too small, the ratio of the ferrite phase increased, and the ductility was insufficient.
[0210] Comparative Example 2-6 has a high Ni content and a low Cr content. In addition, since the proportion of the austenite phase is high, softening is insufficient. In addition, since the Md of the austenite phase is too low, ductility is also insufficient.
[0211] From the above results, it is understood that according to the present invention, a ferrite-austenite duplex stainless steel material that is softer and has higher ductility than conventional ferrite-austenite duplex stainless steel materials can be provided. That is, according to the present invention, by setting the following configurations [1] to
[10] , a ferrite-austenite duplex stainless steel material that is softer and has higher ductility than conventional ferrite-austenite duplex stainless steel materials can be provided.
[0212] [1] A ferrite-austenite duplex stainless steel material having the following composition: containing, by mass, C: 0.001-0.050%, Si: 0.01-0.50%, Mn: 1.0-4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5-3.5%, Cr: 19.6-24.0%, Mo: 0.01-1.00%, Cu: 0.01-1.20%, N: 0.010-0.090%, C+N is less than 0.130%, and the remainder is Fe and impurities,
[0213] The value of Md represented by the following formula (1) is 50.0 to 150.0°C:
[0214] Md=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)
[0215] In the formula, the element symbol represents the content of each element (mass %),
[0216] A metal structure having an austenite phase of 25 to 49 volume %,
[0217] The value of Md represented by the above formula (1) of the above austenite phase is 35.0 to 100.0°C.
[0218] [2] The ferrite-austenitic duplex stainless steel material according to [1], further comprising, by mass, one or more selected from the group consisting of Nb: 0.010-0.500%, Ti: 0.01-0.50%, V: 0.01-0.50%, W: 0.05-0.50%, Co: 0.01-0.30%, B: 0.0002-0.0050%, Sn: 0.010-0.500%, Al: 0.010-0.050%, Mg: 0.0002-0.0100%, Ca: 0.0002-0.0100%, Ta: 0.050% or less, Ga: 0.050% or less, Zr: 0.01-0.50%, and REM: 0.0002-0.0100%.
[0219] [3] The ferrite-austenite duplex stainless steel material according to [1] or [2], wherein, on a mass basis, C: 0.001 to 0.040%, N: 0.010 to 0.080%, C+N less than 0.120%, and the austenite phase accounts for 25 to 40 volume %.
[0220] [4] The ferrite-austenitic duplex stainless steel material according to any one of [1] to [3], wherein the Md value of the austenite phase is 50.0 to 90.0°C.
[0221] [5] The ferrite-austenitic duplex stainless steel material according to any one of [1] to [4], wherein the average grain size of the ferrite phase is 7.0 μm or more.
[0222] [6] The ferrite-austenitic duplex stainless steel material according to any one of [1] to [5], wherein the value of DF represented by the following formula (2) is 50.0 to 80.0:
[0223] DF=7.2(Cr+0.88Mo+0.78Si)-8.9(Ni+0.03Mn+0.72Cu+22C+21N)-44.9(2)
[0224] In the formula, the element symbol represents the content (mass %) of each element.
[0225] [7] The ferrite-austenitic duplex stainless steel material according to [6], wherein the value of DF is 60.0 to 80.0.
[0226] [8] The ferrite-austenitic duplex stainless steel material according to any one of [1] to [7], wherein the tensile strength is 800 MPa or less.
[0227] [9] The ferrite-austenitic duplex stainless steel material according to any one of [1] to [8], wherein the uniform elongation is 30.0% or more.
[0228]
[10] The ferrite-austenite duplex stainless steel material according to any one of [1] to [9], wherein the -4 ~8.3×10 -3 s -1 When a tensile test is performed at a strain rate of 15 to 20%, the ratio of the n value in the strain region of 20 to 25% to the n value in the strain region of 20 to 25% is 0.80 or less.
Claims
1. A ferrite-austenite duplex stainless steel material having the following composition: containing, by mass, C: 0.001-0.050%, Si: 0.01-0.50%, Mn: 1.0-4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5-3.5%, Cr: 19.6-24.0%, Mo: 0.01-1.00%, Cu: 0.01-1.20%, N: 0.010-0.090%, C+N is less than 0.130%, and the remainder is Fe and impurities, The value of Md represented by the following formula (1) is 50.0 to 150.0°C: Md=551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1) In the formula, the element symbol represents the content of each element in mass %, A metal structure having an austenite phase of 25 to 49 volume %, The value of Md represented by the formula (1) of the austenite phase is 35.0 to 100.0°C.
2. The ferrite-austenitic duplex stainless steel material according to claim 1, further comprising, by mass, one or more selected from the group consisting of Nb: 0.010-0.500%, Ti: 0.01-0.50%, V: 0.01-0.50%, W: 0.05-0.50%, Co: 0.01-0.30%, B: 0.0002-0.0050%, Sn: 0.010-0.500%, Al: 0.010-0.050%, Mg: 0.0002-0.0100%, Ca: 0.0002-0.0100%, Ta: 0.050% or less, Ga: 0.050% or less, Zr: 0.01-0.50%, and REM: 0.0002-0.0100%.
3. The ferrite-austenite duplex stainless steel material according to claim 1 or 2, wherein, on a mass basis, C: 0.001-0.040%, N: 0.010-0.080%, C+N is less than 0.120%, and the austenite phase is 25-40 volume %.
4. The ferrite-austenite duplex stainless steel material according to any one of claims 1 to 3, wherein The Md value of the austenite phase is 50.0 to 90.0°C.
5. The ferrite-austenite duplex stainless steel material according to any one of claims 1 to 4, wherein The average grain size of the ferrite phase is 7.0 μm or more.
6. The ferrite-austenite duplex stainless steel material according to any one of claims 1 to 5, wherein The value of DF represented by the following formula (2) is 50.0 to 80.0: DF=7.2(Cr+0.88Mo+0.78Si)-8.9(Ni+0.03Mn+0.72Cu+22C+21N)-44.9(2) In the formula, the element symbol represents the content of each element in mass %.
7. The ferrite-austenite duplex stainless steel material according to claim 6, wherein: The value of DF is 60.0 to 80.
0. 8 . The ferrite-austenitic duplex stainless steel material according to claim 1 , which has a tensile strength of 800 MPa or less. 9 . The ferrite-austenitic duplex stainless steel material according to claim 1 , which has a uniform elongation of 30.0% or more.
10. The ferrite-austenite duplex stainless steel material according to any one of claims 1 to 9, wherein the -4 ~8.3×10 -3 s -1 When a tensile test is performed at a strain rate of 15 to 20%, the ratio of the n value in the strain region of 20 to 25% to the n value in the strain region of 20 to 25% is 0.80 or less.
Citation Information
Patent Citations
Egg box
CA200100A
Austenite-ferrite duplex stainless steel for fuel tank
JP2012126992A
Lean duplex stainless steel with improved corrosion resistance and workability and manufacturing method thereof
JP2019501286A
Cited By
High-surface-quality duplex stainless steel wire rod for cold heading and manufacturing method thereof
CN119876790A
A duplex stainless steel wire rod with high surface quality for cold heading and its manufacturing method
CN119876790B